Mycoplasma synoviae induced eggshell apex abnormalities in commercial layer chicken in Namakkal region of Tamil Nadu - SRIVIGNESH, SUMITHA; KUPPANAN, SUKUMAR; ANNAMALAI, BALASUBRAMANIAM (The Indian Journal of Animal Sciences, 2017)
Commercial Babcock layer chicken, 60 to 70 week-old, in 3 flocks housed in Namakkal region of Tamil Nadu exhibited leg weakness and eggshell abnormalities mainly pronounced in apex region of the egg, suggestive of Mycoplasma synoviae infection. Choanal cleft and oropharyngeal swabs were collected from affected layer flocks in modified Frey's broth medium. Culture and polymerase chain reaction assay amplifying the conserved region of 16S rRNA gene was applied for the confirmation of M. synoviae. The isolates from culture were confirmed by specific amplification of 16S rRNA gene (207 base pair). The current report describe the first eggshell abnormality associated with Mycoplasma synoviae infection in India.